Temperature dependence of magnetic properties of La0.67Sr0.33MnO3 compound by ferromagnetic resonance technique - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
The magnetic properties of bulk La0.67Sr0.33MnO3 sample were studied by ferromagnetic resonance (FMR) technique. The FMR spectra were recorded as a function of temperature between 4 and 300 K. A quite strong signal at low (even zero) field region was observed in addition to the usual FMR peak at room temperatures. In addition to significant absorption at lower fields, a broad FMR lines were observed in contrary to the expected exchange narrowing from any usual ferromagnetic substance, indicating strong local magnetic anisotropies induced at low temperature. The magnetic parameters, such as magnetization, magnetic anisotropies, exchange stiffness constant, and line width have been deduced as a function of temperature between 4 and 300 K by fitting the simulated spectra to the experimental ones. The remarkable exchange anisotropy can be taken as a sign for strong competition between ferromagnetic-antiferromagnetic interactions especially at low temperatures. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: magnetoresistivity; exchange narrowing; magnetic anisotropy; FMR; perovskite; SURFACE ANISOTROPY; LA1-XSRXMNO3; MAGNETORESISTANCE; ESR; MANGANITES; LINEWIDTH; PHASE